Efficacy and safety of traditional Chinese medicines for non-alcoholic fatty liver disease: a systematic literature review of randomized controlled trials - Zuanji Liang; Xianwen Chen; Junnan Shi; Hao Hu; Yan Xue; Carolina Oi Lam Ung (BMC, 2021)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is a common liver disease that may progress into, in the absence of proper treatment, severe liver damage. While the optimal pharmacotherapy for NAFLD remains uncertain and the adherence to lifestyle interventions is challenging, the use of herbal medicines such as traditional Chinese medicines (TCMs) to manage the condition is common. The evidence about TCMs in the management of NAFLD is continuously developing through randomized controlled trials (RCTs). This study aims to identify and evaluate the emerging evidence about the efficacy and safety of TCMs for NAFLD. Methods A systematic literature search was conducted to identify RCTs which investigated TCMs in the management of NAFLD published in 6 electronic databases including PubMed, the Cochrane Library, EMBASE, Web of Science, Scopus and China National Knowledge Infrastructure since inception to September 2020. RCTs comparing TCMs with no treatment, placebo, non-pharmacological and/or pharmacological interventions were included irrespective of language or blinding. The quality of reporting was evaluated using the Consolidated Standards of Reporting Trials Statement extensions for Chinese herbal medicine Formulas (CONSORT-CHM). Risk-of-bias for each study was assessed using the Cochrane risk of bias tool. Results A total of 53 RCTs involving 5997 participants with NAFLD were included in this review. Each included RCT tested a different TCMs giving a total of 53 TCMs identified in this study. Based on the evaluation of the RCT results, TCMs might have various beneficial effects such as improving TCM syndrome score, liver function, and body lipid profile. A range of non-serious, reversible adverse effects associated with the use of TCMs were also reported. However, no conclusion about the efficacy and safety of TCMs in NAFLD can be made. The quality of reporting was generally poor and the risks of bias was mostly uncertain in all trials. Conclusions There is some evidence from RCTs that supported the effectiveness and safety of TCMs for NAFLD. However, no conclusive recommendations can be made due to the questionable quality of the RCTs. Improvement in the RCT protocol, the use of a larger sample size, a setting of multicenter, and a more focused approach in selecting TCMs are recommended for developing high quality evidence about the use of TCMs in managing NAFLD.